2021
DOI: 10.1007/s11695-021-05280-6
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric-Metabolic Surgery Utilisation in Patients With and Without Diabetes: Data from the IFSO Global Registry 2015–2018

Abstract: Background Comparative international practice of patients undergoing bariatric-metabolic surgery for type 2 diabetes mellitus (T2DM) is unknown. We aimed to ascertain baseline age, sex, body mass index (BMI) and types of operations performed for patients with T2DM submitted to the IFSO Global Registry. Materials and Methods Cross-sectional analysis of patients having primary surgery in 2015–2018 for countries with ≥90% T2DM data completion and ≥ 1000 submi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…Long-term studies (10 years) have also reported the nutritional issues associated with DS, particularly with fat-soluble vitamins ( 29 , 30 ). Thus, although the effectiveness of DS is undisputed, it is not commonly performed owing to the high prevalence of complications ( 2 , 31 ).…”
Section: Procedures That Completely Bypass the Foregutmentioning
confidence: 99%
See 2 more Smart Citations
“…Long-term studies (10 years) have also reported the nutritional issues associated with DS, particularly with fat-soluble vitamins ( 29 , 30 ). Thus, although the effectiveness of DS is undisputed, it is not commonly performed owing to the high prevalence of complications ( 2 , 31 ).…”
Section: Procedures That Completely Bypass the Foregutmentioning
confidence: 99%
“…SG can be considered the foundation of most bariatric and metabolic surgeries, as many of the procedures consist of SG. Standalone SG is currently the most commonly performed procedure worldwide, with excellent results ( 2 , 31 ). As mentioned previously, when compared with GB, SG was found to be comparable regarding metabolic improvements as well as having a lower risk of nutritional deficiency ( 12 , 13 , 16 , 23 , 24 ).…”
Section: Procedures That Do Not Bypass the Foregutmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of the satisfactory outcomes achieved by LSG in terms of weight loss and remission of diabetes mellitus, the frequency of LSG has increased in recent years. According to the Fourth IFSO Global Registry Report 2018 (18), LSG has surpassed RYGB (46% vs. 38.2%) on a global scale and it has become the most commonly adopted surgical procedure for metabolic syndrome, accounting for 67% of all such procedures in China. Therefore, the Chinese Guidelines have listed LSG as the procedure of choice.…”
Section: Tailored Selection Of the Proceduresmentioning
confidence: 99%
“…Importantly, some antiepileptics are glucuronidation inducers (phenytoin, phenobarbital and carbamazepine) or inhibitors (sodium valproate), so a pharmacokinetic drug-drug interaction may affect lamotrigine levels. Among the bariatric patients, over 75% are females, and the average age of the operated patient is 42, so many of these patients are of childbearing potential [ 43 ]. Therefore, while valproate (along with lamotrigine) is a first line anticonvulsant for various different epileptic disorders, in many bariatric patients, valproate treatment should not be initiated in case of unsatisfactory lamotrigine treatment following the surgery, due to being highly teratogenic [ 42 ].…”
Section: Clinical Recommendationsmentioning
confidence: 99%